The Influence of Sharia Marketing Strategies on Consumer Purchase Intention toward MSME Products: Evidence from Kuningan Regency, Indonesia - Nur Fitri Prihartini; Barnawi Barnawi; Abu Lubaba Abu Lubaba (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2026)
The purpose of this study was to examine the influence of shariamarketing strategies on consumer interest in buying MSME products inKuningan Regency. The specific objectives of this study were to: identifythefactors that influence consumer interest in sharia-compliant products and services, develop marketing strategies that are aligned with Islamic values, measuretheeffectiveness of sharia marketing campaigns. This study uses a quantitative research approach. Data collectionwascarried out through a survey of 86 consumers in Kuningan Regency. The surveyinstrument is a questionnaire designed to measure respondents' interest insharia- compliant products and services. The results of the study show that there is a positive and significant influence of sharia marketing strategies on consumer buying interest in MSMEproducts in Kuningan Regency. The study also found that the followingfactorsare important in influencing consumer interest in sharia-compliant products andservices: promotion of halal products and services, use of quality and halal rawmaterials, emphasis on ethical business practices, affordable product prices. The results of this study indicate that sharia marketing can be an effectiveway to attract and retain customers for MSMEs in Kuningan Regency. Theregression equation is Y=a+BX or 52.951+0.171X. By adhering to Islamic valuesin their marketing practices, MSMEs can create a more positive image for their business and attract more customers. This study also has implications for government policy. The government can support the growth of MSMEs inKuningan Regency by providing sharia-based marketing promotion and resourcemanagement training. This will help MSMEs in Kuningan Regency to developmore effective marketing strategies and increase sales